2022-RA-1700-ESGO New ultrasonographic markers of borderline ovarian tumours (BOT). (20th October 2022) - Rodriguez, Nadiezhda; Rodriguez, Nicolas; Ayala, Nathalia; Buritica, Catalina; Saravia, Camila; Nastar, Ángela; Ramírez, Natalia; Esquivel, Alba
Abstract : Introduction/Background: The most common signs of BOT on ultrasound (US) are reported to be: a septate cyst with solid component and/or mural nodules containing blood vessels in papillary projections. However, we describe ultrasonographic markers additional for the diagnosis of BOT Methodology: A retrospective study at a tertiary referral university hospital with a gynaecological oncology unit, from patients who underwent surgery between 2012 and 2022 with previous transvaginal ultrasound performed by gynaecologists or radiologists. Patients with a diagnosis of BOT by histopathological findings were included. Descriptive analyses were performed. Results: Of 18 patients diagnosed with BOT, with a mean age of 39 (±) 17 years, 11 (73%) were premenopausal, their median CA 125 was 115 (±) 32 U/mL. The mean maximum diameter of the lesion was 54 (±) 72 mm, 9 (60%) were described as unilocular solids, 5 (33%) as multilocular solids and 1 (7%) as unilocular. In addition to the classic criteria such as vascularization in the papilla found in 15 (83%) of the cases, we found novel characteristics such as: a low level of echogenicity content in 14 (78%) and a pattern of microcystic tissue that resembles a group of small bubbles in 12 (67%) of these tumors. Furthermore, when these three characteristics were positive, the tumors were diagnosed by histopathology as being of serous origin. Conclusion: This study proposes additional characteristics that are of interest for the approach and diagnosis of BOT by ultrasound.